Development of a complex mathematical model of the state of a channel of multi-antenna radio communication systems - Kalantaievska, Svitlana; Kuvshynov, Oleksii; Shyshatskyi, Andrii; Salnikova, Olha; Punda, Yurii; Zhuk, Pavlo; Zhuk, Olesia; Drobakha, Hryhorii; Shabanova-Kushnarenko, Lyubov; Petruk, Sergii (Eastern-European Journal of Enterprise Technologies, 2019)
The complex mathematical model of the state of the channel of multi-antenna radio communication systems is developed. The model takes into account: the effect of intentional noise and signal fading, the number of receiving antennas, Doppler effect, correlation coefficient, speed and direction of the receiver and the transmitter, intersymbol interference, phase jitter and inclination of the constellation matrix. Simulation of the state of the channel of multi-antenna radio communication systems is carried out for each individual antenna channel, after which a generalized estimate is formed at the output. The development of the proposed integrated mathematical model is due to the need to improve the accuracy of the description of the channel state of multi-antenna radio communication systems with an acceptable computational complexity. The proposed model allows to improve the accuracy of the description of the state of the channel of multi-antenna radio communication systems by taking into account additional destabilizing factors, thereby increasing the accuracy of the channel state assessment. I would like to note that at the same time there is an increase in the computational complexity at the level of 5-7% due to an increase in the number of evaluated indicators. The mentioned complex mathematical model should be used in radio stations with a programmable architecture to increase their noise immunity by increasing the accuracy of the evaluation of the characteristics of the receiving and transmitting path relative to the state of the channel. The research of the correlation between antennas of multi-antenna radio communication systems was conducted. The results show that in the presence of a line of sight between the receiver and the transmitter, the signal correlation is high and therefore a small increase is expected from the use of several antennas, and in the absence of line of sight conditions, the signal correlation is low